Ferulic acid alleviates the symptoms of diabetes in obese rats - Yuan Song; Taigang Wu; Qinhe Yang; Xiaoyin Chen; Mingfu Wang; Yong Wang; Xichun Peng; Shiyi Ou (Journal of Functional Foods, 2014)
The effect of ferulic acid on biochemical and histological properties, mRNA expression of HO-1 and GST in the liver and heart were investigated in obese, diabetes rats after ferulic acid administration for 16 weeks. The results showed that ferulic acid (60 mg/kg) decreased the activities of ALT, AST, CK, and LDH in the serum, by 53.5, 33.6, 47.8, and 405.5% respectively; and reduced cell apoptosis from 16.55 to 9.11% in the liver, and 11.27 to 5.09% in the heart. Ferulic acid significantly increased the antioxidant activity in the plasma, liver, and heart, and upregulated the mRNA expression of HO-1 and GST in the cells of liver and heart of the diabetes animals. Moreover, ferulic acid maintained the body weight, significantly decreased serum glucose and lipid, and advanced glycation end products in the plasma, liver, and heart. It can be concluded that ferulic acid can alleviate late-stage diabetes in obese rats.